2018
DOI: 10.1021/jacs.8b02303
|View full text |Cite
|
Sign up to set email alerts
|

Remarkable Acid Catalysis in Proton-Coupled Electron-Transfer Reactions of a Chromium(III)-Superoxo Complex

Abstract: Much enhanced acid catalysis was observed in oxygen atom transfer (OAT) reactions by a mononuclear nonheme Cr(III)-superoxo complex, [(Cl)(TMC)Cr(O)] (1), in the presence of triflic acid. In the acid-catalyzed reactions, the reactivity of 1 in OAT of thioanisole was enhanced significantly, showing more than 10-fold acceleration in rate. Electron transfer (ET) from electron donors to 1 also occurred only in the presence of HOTf. The enhanced reactivity of 1 by HOTf was explained by proton-coupled electron trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
40
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(47 citation statements)
references
References 49 publications
7
40
0
Order By: Relevance
“…•-)] + and outer-sphere one-electron donors, which are the coordinatively saturated metal complexes. 126 The difference of 3.5 in the log K values between thioanisole and [Fe II L 3 ] 2 + was determined, which agrees that the observed log k ox value of thioanisole (red point no. 11) is 3.5 times bigger than the log k et value in blue line (Figure 16).…”
Section: •-supporting
confidence: 84%
See 3 more Smart Citations
“…•-)] + and outer-sphere one-electron donors, which are the coordinatively saturated metal complexes. 126 The difference of 3.5 in the log K values between thioanisole and [Fe II L 3 ] 2 + was determined, which agrees that the observed log k ox value of thioanisole (red point no. 11) is 3.5 times bigger than the log k et value in blue line (Figure 16).…”
Section: •-supporting
confidence: 84%
“…•-)] + in the presence of HOTf (1.0 mM) in CH 3 CN at 233 K was determined to be 3.5(3) M −1 s −1 , which is 10 4 times bigger than that in the absence of HOTf (3.6 × 10 −4 M −1 s −1 ). 126,127 As shown in Figure 14, the k ox value increased with an increase in HOTf concentration, which is proportional to [HOTf] 2 [Eq. (13)].…”
Section: Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…11 The strong Lewis acid Sc 3+ and the strong Brønsted acid CF 3 SO 3 H have been used to activate Fe(IV) and Mn(IV) oxo complexes, 12,13 as well as metal superoxo species. 14,15 There is also much interest in the use of the relatively weak Lewis acid, Ca 2+ , to activate M=O because of its relevance to the CaMn 4 O 5 cluster in Photosystem II; although as expected, its effect is usually much smaller than those of Sc 3+ or BF 3 . For example, Agapie et al reported that Ca 2+ and other metal ions can increase the reduction potentials (E 0 ) of manganese oxo clusters, and there is a linear correlation between E 0 and pK a of the metal ions.…”
Section: Introductionmentioning
confidence: 94%